Development of the North Sakhalin aqua territorial production complex (ATPC) program: View from the past - Valentina Zolotova (European Regional Science Association (ERSA), 2014)
Formation of ATMC program was executed using the developed economics and mathematics model in which manufacturing and special structure of the Oil and Gas complex was determinated. Basic condition of determination of the optimization task and development of the appropriate model was mutual discussion of the following structure elements of ATMC: deposits of hydrocarbon resources in the land and in the shelf; plant on manufacturing of the ice-resistant platforms providing mining in the shelf; steel structures plant production of which is necessary for manufacturing ice resistant platforms; complex supply bases for sea deposits; construction and installation organizations; aggregated objects of the construction materials industry; power plants and power transmission lines; sectors of pipeline and railroad transportation; enterprises on processing of the hydrocarbon resources, labor resources and population; water resources; total of other objects of Sakhalin economics. In process of solution it was required to determine the dynamics of oil, gas and condensate mining, scales and order of mining og the sea oil, gas and condensate deposits, to compose schemes of distribution of hydrocarbon resources for processing, scheme of placement of the manufacturing objects and objects oriented to maintenance of the oil and gas complex, placement of the elements of manufacturing infra of areawide level with following the conditions below: - following the volumes of oil mining in ATMC; following the industrial restrictions on change of oil mining in land in terms of the alloted periods of prognosis periods and areals ; providing the requirements of the other industrial objects places in the alloted areas , services of infra of ther areawide scale and territory resources; This model helped to make calculations taking into account the selected strategy of development of the sea oil and gas resources depending on fixed intensity of the deposit development in the island. It is clear that the prognosis could be made with taking into account the functioning of the state enterprises. Search of opportunities of use of the above model in the situation when private enterprises and enterprises with foreign investments work caused the additional calculations. These calculations meant economical effectiveness of the investments for development of the deposits and forming the whole complex. Analysis of influence of several factors on economical effectiveness was made. The factors are prices for hydrocarbon resources, volumes of mining, scales of investments. As the condition of realization of the Sakhalin projects, in which foreign companies participated, was Law Agreement about Division of the Product, so author composed the model of coordination of the interests of development participators. In process of decision profit ratio of the profit obtained by Russia and foreign companies based on project economics and royalty was determined.
Keywords: 330; Formation of ATMC program; economics and mathematics model; North Sakhalin Aqua Territorial Manufacturing Complex; the model of coordination of the interests